OPTIMIZE (CIPEEX, 2025)
The Optimize tool aims to refine financial resources and simplify expense and inventory management for companies. In a quick description of the system's functionalities, the tool provides real-time monitoring of cash flow, expenses and inventory. The methodology involves integrating advanced features such as real-time monitoring, product expiry control and stock addressing, allowing for precise order management and cost optimization. The results demonstrate how the tool generates comprehensive reports on sales, profits, product usage trends and stock shortage forecasts. These reports provide insights into key performance metrics such as revenue, profit margins and best-selling products, aiding decision-making and resource allocation. The findings highlight Optimize's ability to offer a unified view of financial data and expenses, allowing companies to reduce costs without compromising quality. There are also opportunities to improve inventory management through data-based analysis and predictive reports, contributing to greater operational efficiency and control of the Optimize user company's financial situation.
Keywords: financial management; expense optimization; stock control; cash flow